PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA JASA FITNESS CENTER DI SAMARINDA CLUB FITNESS - Ahmad Afifuddin Rozib (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT Health is a very important asset for daily activities. Sports a way maintaining health. One sport that is currently popular is fitness. Obviously fitness shall be done at the fitness center (gym). There are many established fitness centers in the Samarinda. However, in fact fitness centers are less noticing their customers needs. Based on those facts above legal protection toward consumers. Consumers protection has been regulated in Law number 8 of 1999 on Consumer Protection. The law is the legal base that integrate and strengthen law enforcement in the field of consumer protection. Other consumer protection regulations governing service fitness center (gym) is Law number 3 of 2005 on National Sports System, Act number 36 of 2009 on Health, and the Indonesian Government Regulation number 16 of 2007 on the Implementation of Sport. The purpose of this study is to determine the protections that provided by the fitness center for consumer by the Consumer Protection Act. This study uses juridical normative and normative empiric research, it has purposed to obtain depth information of the object being studied. The research was conducted in Samarinda Club Fitness Center. Based on these results it can be seen that the Fitness too idea services to their customers at best. Services given the Fitness center, intended that consumers can obtain their rights as stipulated in Article 4 of Law number 8 of 1999 on Consumer Protection. Regarding to Article 4 of the Consumer Protection Act apart the rights of consumers, business service fitness center meets these rights. Some effect foward dispute between the Fitness and the consumer is to deliberation, if it is not succeded then the consumer can sue through the court. The settlement of resolution dispute efforts aimed to provide legal protection towars consumers. Keywords: Law Protection, Consumer Protection, Consumer Fitness Centre.